2015
DOI: 10.1128/jvi.01452-15
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Transmission of Viral Populations with Vesicles

Abstract: A common paradigm holds that during cell-to-cell transmission, viruses behave as lone soldiers. Recently, we discovered not only that enteroviruses are transmitted via vesicles as populations of viral particles but also that this type of transmission enhances their infection efficiency (Y. H. Chen et al., Cell 160:619 -630, 2015). This mechanism could be advantageous for the overall fitness of the viral population, promoting genetic interplay by enabling viral quasispecies to collectively infect a susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 21 publications
(23 reference statements)
2
38
0
Order By: Relevance
“…Indeed, we have demonstrated here that being wrapped inside vesicles may confer to the virus a number of advantages, including a greater efficiency of infection and the ability to stimulate phagocytosis. Therefore, these vesicles can facilitate the spread of the virus to other susceptible cells by collectively transferring multiple viral genomes into the cytoplasm (21). Also, we demonstrated that the vesicles confer to MsV resistance to high temperature.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, we have demonstrated here that being wrapped inside vesicles may confer to the virus a number of advantages, including a greater efficiency of infection and the ability to stimulate phagocytosis. Therefore, these vesicles can facilitate the spread of the virus to other susceptible cells by collectively transferring multiple viral genomes into the cytoplasm (21). Also, we demonstrated that the vesicles confer to MsV resistance to high temperature.…”
Section: Discussionmentioning
confidence: 65%
“…This represented a breakthrough in virology as, until then, a virus was considered either enveloped or nonenveloped, without the useful in repelling specific antibodies, thus providing an important advantage to those viruses within their hosts (20,21). Given the natural hosts of marseilleviruses, this does not seem to be applicable, as amoebas do not possess an adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…not in vesicle) viral particles [11••]. This brings up the intriguing possibility that vesicular travel of viral populations may be nature's way of generating high multiplicities of infection in order to enhance viral propagation and survival [33]. In particular for RNA viruses, having a high multiplicity of infection can provide greater opportunities for genetic cooperativity [34•,35•].…”
Section: Vesicles Enable High Multiplicity Of Infection and Can Facilmentioning
confidence: 99%
“…Furthermore, after replication and assembly into new viral particles, all (+) ssRNA viruses can coopt membranes as carriers to be transported out of cells non-lytically and be transmitted to other susceptible hosts. These newly synthesized viruses can emerge as single membrane enveloped particles or as populations of viral particles, transported together to the next cell within membrane-bound vesicles [3,4]. In particular, the latter which enables trafficking of viral populations en masse from cell to cell can significantly enhance viral infectivity and replicative fitness [3,4].…”
Section: Introductionmentioning
confidence: 99%